The space of immigrant discourse in the European press: Lessons from the "refugee crisis" - Zaborowski, Rafal; Hovden, Jan Fredrik (MedieKultur: Journal of media and communication research, 2024)
In this article we offer a new analysis of two never previously combined datasets on press coverage of the “refugee crisis” in Europe in 2015. Consisting of twenty-nine newspapers from eleven countries, the data provides an unprecedented sample of the European press in the time of crisis. Using forty-six characteristics of frames, agents, aids and protective measures mentioned in the articles, we demonstrate an innovative analytic approach, where multiple correspondence analysis is used to construct and explore main differences in an European statistical space of articles (N=1674) and a sevenfold statistical typology of stories concerning the crisis. The findings indicate that while national and regional differences in the coverage are salient in explaining the balance of humanitarian or securitisation attitudes, it is the intra-national differences that emerge as particularly significant, revealing rich complexity of texts and contexts. Analysing the structuration of stories as space of press coverage allows us to move beyond isolated variables and look at how individual articles are more divided in their fundamental narratives.